Pengaruh Motivasi Berprestasi, Emotional Quotient, dan Spritual Quotient Terhadap Prestasi Kompetisi Sains Madrasah Siswa - Ria Deswita; Febria Ningsih; Darsi Darsi (Journal on Education, 2023)
This research is motivated by the importance of student achievement in education. student achievement in education is usually known after going through a test or a competition. One of the competitions that is always contested every year from the city/district level to the national level is the Madrasah Science Competition (KSM). KSM is a competition held within the Kementerian Agama for Tsanawiyah or Aliyah level students. Achievement in a competition can be influenced by several factors, one of which is achievement motivation. In addition, at this time the assumption that human intelligence is only based on the intellectual dimension is no longer valid. There is something called Emotional Intelligence or EQ (Emotional Quotient) and SQ (Spiritual Quotient). This research is a research with a quantitative approach, and the method used is survey method. The population in this study were all 55 students at the madrasah aliyah in Sungai Penuh who took part in KSM. The sample consisted of 38 people who were selected randomly or by simple random sampling technique. Hypothesis testing is done by simple regression analysis. Based on data analysis, it was found that: 1) There is an influence between achievement motivation on student KSM achievement in Sungai Penuh City by 27.3% 2) There is an influence of emotional quotient on student KSM achievement in Sungai Penuh City by 21.4% 3) There is an influence the spiritual quotient for KSM student achievement in Sungai Penuh City is 12.8%